EVALUASI RASIONALITAS PENGGUNAAN DAN PEMBERIAN OBAT PADA PASIEN HIPERTENSI GERIATRI DI PUSKESMAS TAJINAN PERIODE JANUARI – DESEMBER 2019 - Luluk Anisyah; Wibowo Wibowo (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Increasing the number of elderly causes an increase in health problems one of which is associated with hypertension which can cause complications and death. The purpose of this study was to determine the description and accuracy of the use of antihypertensive drugs in geriatric patients who were diagnosed with hypertension at the Tajinan Primary Health in Malang in the period January-December 2019. This study was an observational or non-experimental study conducted using retrospective medical record data. The measuring instrument used was the data collection sheet from the medical record, the Consensus for Hypertension Management 2019 to see the accuracy of indications, patient accuracy, drug accuracy, and dose accuracy. Data analysis using Correlation Test. The results of the correlation analysis showed that the resulting Standardize estimates were 0.002 (p <0.05) which showed that there was a significant relationship between sexes with the occurrence of hypertension. The results of the correlation analysis showed that the resulting Standardize estimates were 0.001 (p <0.05) which means that there was a significant relationship between the accuracy of the types of antihypertensive drugs used in hypertensive patients. The conclusion is that the rationality evaluation of the use and administration of drugs in hypertensive patients at the Tajinan Primary Health in Malang based on the 2019 Hypertension Management Consensus guidelines shows the accuracy both in terms of indication, drug, patient and dose.